Chinese students' motivation in physical activity: Goal profile analysis using Nicholl's achievement goal theory - Wang, C.; Liu, W.; Sun, Y.; Lim, B.; Chatzisarantis, Nikos (Taylor & Francis Inc., 2010)
One of the contributing factors for the increased obesity rate in China is the reduction of physical activity and exercise. With this as the backdrop, understanding Chinese students' motivation toward physical education (PE) and physical activity is a worthy area of study. The purpose of this study was to examine Chinese students' motivation for physical activity using Nicholl's (1989) achievement goal approach. A total of 984 Chinese students from six schools in mainland China participated in the survey measuring achievement goals, motivational regulation, perceived competence, attitudes toward PE, and physical activity. Using cluster analysis, four goal profiles were found. Three clusters were similar to the "highly motivated," "moderately motivated," and "lowly motivated" clusters found in previous study (Wang, Chatzisarantis, Spray, & Biddle, 2002). One additional cluster with a "moderate task/moderate ego/high perceived competence" goal profile (Cluster 2) consisted of 39.6% of the sample and was unique to the Chinese sample. This cluster was found to have the lowest external regulation and high identified regulation and intrinsic motivation; they also had the most positive attitudes toward PE and reported highest participation in physical activity. There were gender differences among the four goal profiles. The majority of the Chinese students did not have an ideal goal profile adaptive for long term motivation. Therefore, there is a need for intervention to increase the task orientation and perceived competence of Chinese students in PE.